Resin composition
By using a composition of bismaleimide resin, liquid rubber resin and filler in high-frequency printed circuit board materials, the problem that existing materials are difficult to meet high glass transfer temperature and low dielectric loss at the same time, and excellent electrical performance and heat resistance are achieved.
Patent Information
- Application Number
- CN202311217249.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-23
- Filing Date
- 2023-09-20
- Publication Date
- 2025-02-25
AI Technical Summary
While increasing the glass transfer temperature, existing low dielectric formulas are difficult to meet the dual requirements of high-frequency printed circuit boards for low dielectric loss and high glass transfer temperature.
The resin composition mainly consists of bismaleimide resin, combined with liquid rubber resin and filler, and the electrical properties of the material are optimized by adjusting the proportion of the composition and adding coupling agents, catalysts and flame resistant agents.
It achieves a balance between high glass transfer temperature (greater than or equal to 250℃) and low dielectric loss (greater than or equal to 0.002) in the high frequency range, while reducing the dielectric constant (greater than or equal to 3.2), improving the heat resistance and peel strength of the material.
Smart Images

Figure BDA0004459448970000031 
Figure BDA0004459448970000041 
Figure BDA0004459448970000081
Abstract
Description
Technical Field
[0001] The present invention relates to a composition, and in particular to a resin composition. Background Art
[0002] In recent years, due to the development of 5G communication and millimeter wave communication, mobile phones, base stations, servers, etc. are applied to higher frequencies (6-77GHz). Therefore, higher-frequency substrate materials must be used to be suitable for 5G high frequencies, and copper-clad laminate materials must also be developed towards the goal of lower dielectric properties. In the current low-dielectric formula, a certain proportion of liquid rubber can be added to reduce the dielectric loss to below 0.0020, but its glass transition temperature will be low. Therefore, how to develop materials with excellent electrical properties and meet the characteristics of high-frequency printed circuit boards, such as materials with high glass transition temperature and low dielectric loss, is still one of the problems that need to be solved in the technical field of printed circuit boards. Summary of the invention
[0003] The present invention provides a resin composition, comprising: based on the total weight of the resin composition, 30 to 60 weight percent of a bismaleimide resin; 1 to 10 weight percent of a liquid rubber resin; and 20 to 50 weight percent of a filler.
[0004] In one embodiment of the present invention, the bismaleimide resin includes DCPD-BMI, KI-50P, KI-70 or a combination thereof.
[0005] In one embodiment of the present invention, the liquid rubber resin includes LDM-03-07, LDM-02, 1,2-SBS or a combination thereof.
[0006] In one embodiment of the present invention, the resin composition further comprises 0.1 wt % to 3 wt % of a coupling agent and 0.1 wt % to 2 wt % of a catalyst.
[0007] In one embodiment of the present invention, the resin composition further comprises 10 wt % to 20 wt % of a flame retardant.
[0008] The present invention provides an electronic component, comprising a substrate formed from the above resin composition.
[0009] In one embodiment of the present invention, the glass transition temperature of the substrate is greater than or equal to 250°C.
[0010] In one embodiment of the present invention, the substrate has a dielectric loss less than or equal to 0.002 at a frequency of about 10 GHz.
[0011] In one embodiment of the present invention, the substrate has a dielectric constant less than or equal to 3.2 at a frequency of about 10 GHz.
[0012] In one embodiment of the present invention, the substrate is a copper foil substrate.
[0013] Based on the above, the resin composition of the present invention can achieve high glass transition temperature (greater than or equal to 250°C) and low dielectric loss (less than or equal to 0.002) in the application of copper foil substrate. In addition, the resin composition of the present invention has a non-polar backbone structure, so it is not easily polarized in an electric field, thereby significantly reducing its dielectric constant (less than or equal to 3.2). DETAILED DESCRIPTION
[0014] The following are examples of the present invention. The implementation details provided in the examples are for illustration purposes only and are not intended to limit the scope of the present invention. Anyone with ordinary knowledge in the art can modify or change these implementation details according to the needs of the actual implementation.
[0015] Ranges may be expressed herein as from "about" one particular value to "about" another particular value, which may also be expressed directly as one particular value and / or to another particular value. When expressing the range, another embodiment includes from the one particular value and / or to the other particular value. Similarly, when a value is expressed as an approximation by using the antecedent "about," it will be understood that the particular value forms another embodiment. It will be further understood that the endpoints of each range may be expressly related to or independent of the other endpoint.
[0016] In this document, non-limiting terms (such as may, could, for example, or other similar terms) mean optional or optional implementation, inclusion, addition, or presence.
[0017] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the present invention belongs. It will also be understood that terms (such as those defined in commonly used dictionaries) should be interpreted as having a meaning consistent with their meaning in the relevant technical context and should not be interpreted in an idealized or overly formal sense unless explicitly defined as such herein.
[0018] Herein, the so-called “divalent organic group” is an organic group having two bonding positions, and the “divalent organic group” can form two chemical bonds through the two bonding positions.
[0019] The present invention provides a resin composition, comprising: based on the total weight of the resin composition, 30 to 60 weight percent of bismaleimide (BMI) resin; 1 to 10 weight percent of liquid rubber resin; and 20 to 50 weight percent of filler. The present invention uses bismaleimide resin in combination with liquid rubber resin and filler to improve the heat resistance of high-frequency substrate materials and reduce the dielectric loss of high-frequency substrate materials.
[0020] In some embodiments, based on the total weight of the resin composition, the weight percentage of the maleimide resin is 30 wt % to 60 wt %, such as 35 wt %, 45 wt % or 55 wt %.
[0021] In some embodiments, the maleimide resin has a structure represented by the following formula (1):
[0022]
[0023] Wherein, L represents a dicyclopentadienyl group, a divalent organic group derived from a phenolic compound, or a combination thereof,
[0024] L 1 and L 2 each represents a divalent organic group derived from a phenolic compound, and
[0025] m represents an integer of 0 to 18.
[0026] In some embodiments, the phenolic compound comprises phenol. In some embodiments, the divalent organic group is preferably a divalent organic group comprising a maleimide group. In some embodiments, L is preferably a combination of a dicyclopentadienyl group and a divalent organic group derived from a phenolic compound. In some embodiments, L represents
[0027] or a combination thereof, wherein * represents a bonding position. In some embodiments, L 1 and L 2 Each expressed Where * indicates the bonding position.
[0028] In some embodiments, the maleimide resin has a structure represented by the following formula (2):
[0029]
[0030] Wherein, m represents an integer of 0 to 18, preferably 2 to 10.
[0031] For example, the synthesis method of maleimide resin includes the following steps. First, 1 mol of dicyclopentadiene phenolic resin (trade name ERM6140, manufactured by Songyuan Company, weight average molecular weight 1,300) and 1.25 mol of 4-halonitrobenzene (wherein the halogen can be fluorine, chlorine, bromine or iodine) are added to 6 mol of dimethylacetamide (DMAC) as a reaction solvent, and reacted at a temperature of 120° C. for 300 minutes to perform a nitration reaction. Then, hydrogen is introduced and reacted at a temperature of 90° C. for 480 minutes to perform a hydrogenation reaction to form a modified dicyclopentadiene type diamine. Next, 3 mol of maleic anhydride and 9.7 wt % of toluenesulfonic acid were added and reacted at 120° C. for 420 minutes to obtain a second resin, which is a bismaleimide resin (DCPD-BMI) having a dicyclopentadiene structure as the main chain, having the structure represented by the above formula (2), and an average molecular weight of 800 to 10,000, preferably 1,000 to 4,000.
[0032] In some embodiments, the weight percentage of the liquid rubber resin is 1 wt % to 10 wt %, such as 2 wt %, 5 wt % or 8 wt %, based on the total weight of the resin composition. In some embodiments, the liquid rubber resin includes LDM-03-07, LDM-02, 1,2-SBS or a combination thereof.
[0033] In some embodiments, the weight percentage of the filler is 20% to 50% by weight, such as 30%, 35% or 40% by weight, based on the total weight of the resin composition. In some embodiments, the filler has a spherical shape, and the particle size (D50) of the filler is 0.3 μm to 3 μm. In some embodiments, the maximum particle size (D99) of the filler is not greater than 10 μm. In some embodiments, the filler contains a surface modification of acrylic or vinyl. In some embodiments, the filler is a silica (SiO2) filler provided by Sanshiji Company.
[0034] In some embodiments, the resin composition further comprises a coupling agent. In some embodiments, the weight percentage of the coupling agent is 0.1 wt % to 3 wt %, such as 0.5 wt %, 1 wt % or 1.5 wt %, based on the total weight of the resin composition. Adding a coupling agent can enhance the compatibility and crosslinking degree of the resin composition for glass fiber cloth and powder. In some embodiments, the coupling agent content in the resin composition is 0.1 parts per hundred parts of resin (phr) to 3phr of coupling agent per hundred parts of resin. In some embodiments, the coupling agent content in the resin composition is about 1phr. In some embodiments, the coupling agent is a siloxane coupling agent. In some embodiments, the coupling agent is vinyl silane or acrylic silane. In some embodiments, the coupling agent is a coupling agent provided by Dow Chemical (DOW) under the trade name Z-6030.
[0035] In some embodiments, the resin composition further comprises a flame retardant. In some embodiments, the weight percentage of the flame retardant is 10 wt % to 20 wt %, such as 12 wt %, 15 wt % or 18 wt %, based on the total weight of the resin composition. In some embodiments, the flame retardant is a phosphorus-based flame retardant. In some embodiments, the flame retardant is a flame retardant with a trade name of PX200 provided by Daba Chemical Company.
[0036] In some embodiments, the resin combination further comprises a catalyst. In some embodiments, the weight percentage of the catalyst is 0.1 wt % to 2 wt %, such as 0.5 wt %, 1 wt % or 1.5 wt %, based on the total weight of the resin combination. In some embodiments, the catalyst content in the resin combination is preferably 0.5 phr to 1.2 phr. In some embodiments, the catalyst is a catalyst called DCP provided by ARKEMA.
[0037] The resin composition of the present invention can be suitable for forming a substrate for an electronic component. In some embodiments, the substrate is a copper foil substrate. In some embodiments, the substrate has the following specifications: a glass transition temperature greater than 250°C (e.g., about 250°C to 260°C); and a dielectric loss of less than or equal to about 0.002 (e.g., about 0.0015 to 0.0019). In some embodiments, the dielectric constant of the substrate is less than or equal to about 3.2 (e.g., about 3.0 to 3.15). In some embodiments, the peel strength of the substrate is greater than or equal to about 4.5 lb / in (e.g., about 4.5 lb / in to 5.2 lb / in). In some embodiments, the heat resistance of the substrate passes the test.
[0038] The following is a detailed description of the implementation and efficacy of the present invention using the copper foil substrates made of the resin compositions of the Examples and Comparative Examples. However, the present invention is not limited to the following Examples and Comparative Examples.
[0039] According to the composition ratio in Table 1 below, the resin composition was mixed with butanone to form a varnish of a thermosetting resin composition. The obtained varnish was impregnated with Nan Ya fiberglass cloth (Nan Ya Plastics Co., Ltd., cloth type 1078LD) at room temperature, and then dried for several minutes at about 130°C (impregnation machine temperature) to obtain a prepreg with a resin content of 60% by weight. Then, four prepregs were stacked between two copper foils of about 35μm thickness and heated at 25kg / cm 2 The film was kept at a constant temperature of 85°C for 20 minutes under a pressure, then heated to 210°C at a heating rate of 3°C / min, and then kept at a constant temperature for 120 minutes, and then slowly cooled to 130°C to obtain a 0.5 mm thick copper foil substrate.
[0040] In Examples 1 to 6, the "DCPD-BMI" used is a bismaleimide resin (DCPD-MI) having a structure represented by the aforementioned formula (2).
[0041] In Examples 2 to 4, the "KI-50P" and "KI-70" used are maleimide resins sold by KI Chemical Industry Co., LTD., Japan, under the trade names of KI-50P and KI-70 series, respectively.
[0042] In Example 1, Example 2, Example 4, Example 5 and Comparative Example 5, the "LDM-03-07" and "LDM-02" used are liquid rubber resins sold by Dainippon Ink & Chemicals, Inc. under the trade names of LDM-03-07 and LDM-02 series, respectively.
[0043] In Example 3, Example 6, Comparative Example 1, Comparative Example 3 and Comparative Example 5, the "1,2-SBS" used is a liquid rubber resin sold by NIPPON SODA Co., Ltd. under the trade name of 1,2-SBS series.
[0044] In Comparative Examples 1 to 6, the “RI 257” and “RI 184” used are liquid rubber resins sold by Crayvalley under the trade names of RI 257 and RI 184 series, respectively.
[0045] In Examples 1 to 6 and Comparative Examples 1 to 6, the "PX200" used is a flame retardant sold by Dahachi Chemical Co., Ltd. under the trade name of PX200 series.
[0046] In Examples 1 to 6 and Comparative Examples 1 to 6, the “DCP” used is a catalyst sold by ARKEMA under the trade name of DCP series.
[0047] In Examples 1 to 6 and Comparative Examples 1 to 6, the “Z-6030” used is a siloxane coupling agent sold by Dow Chemical Company under the trade name of Z-6030 series.
[0048] In Examples 1 to 6 and Comparative Examples 1 to 6, the SiO 2 used is a silica filler sold by Sanshiki Company.
[0049] The glass transition temperature, dielectric constant, dielectric loss, peel strength and heat resistance of the copper foil substrate were evaluated in the following manner, and the evaluation results are listed in Table 1.
[0050] Glass transition temperature (Tg)
[0051] The glass transition temperature (Tg) of the resin composition in the copper foil substrate is measured by a dynamic mechanical analyzer (DMA). The higher the Tg, the better the ability of the resin composition to resist phase change, that is, the better the heat resistance.
[0052] Dielectric constant (Dk)
[0053] The dielectric constant at a frequency of about 10 GHz was measured using a dielectric analyzer (Model E4991A, manufactured by Agilent Technologies, Inc.) The smaller the dielectric constant, the better the dielectric properties of the resin composition in the copper foil substrate.
[0054] Dielectric loss (dissipation factor, Df)
[0055] The dielectric loss at a frequency of about 10 GHz was measured using a dielectric analyzer (Model E4991A, manufactured by Agilent Technologies). The smaller the dielectric loss, the better the dielectric properties of the resin composition in the copper foil substrate.
[0056] Peel strength
[0057] The peel strength between the prepreg and the copper foil was tested according to the IPC-TM-650-2.4.8 test method.
[0058] Heat resistance
[0059] The copper foil substrate sample is heated in a pressure cooker at 120℃ and 2atm for 120 minutes, then immersed in a soldering furnace at 288℃, and the time required for the board to burst is recorded. If the board burst time exceeds 10min, it is indicated as "OK", and if the board burst time is shorter than 10min, it is indicated as "NG".
[0060] [Table 1]
[0061]
[0062] <Evaluation Results>
[0063] As shown in Examples 1 to 6 of [Table 1], the copper foil substrate prepared by the resin composition having the composition ratio of the present invention has a measured Tg higher than 250°C, a dielectric loss Df less than 0.002, and a dielectric constant Dk less than 3.2. Moreover, the copper foil substrates of Examples 1 to 6 also exhibit good peel strength (≥4.5 lb / in) and good heat resistance.
[0064] However, it can be seen from Comparative Examples 1 to 6 in [Table 1] that when the weight percentage of the maleimide resin is less than 30 wt % or greater than 60 wt %, the measured Tg is lower than 250° C. In addition, it can be seen from Comparative Examples 1, 3 and 5 that when the weight percentage of the liquid rubber resin is greater than 10 wt %, the measured Tg is even lower than 165° C., and the performance of the peel strength and heat resistance is also unsatisfactory.
[0065] In summary, the resin composition of the present invention is mainly composed of bismaleimide resin and liquid rubber resin. In addition to being able to provide high glass transition temperature and low dielectric loss at the same time, it also has a non-polar backbone structure, so it is not easily polarized in an electric field, and its dielectric constant can be greatly reduced. In addition, the resin composition of the present invention can be directly or indirectly applied to copper foil substrates, and can be further processed to become other electronic components or electronic products (such as circuit boards or copper foil substrates) for people's livelihood, industrial or suitable applications. In addition, the resin composition of the present invention is helpful in the application of copper foil substrates for the reduction of dielectric constant, the improvement of peel strength and / or the improvement of heat resistance.
[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A resin composition, characterized in that include: Based on the total weight of the resin composition, 30 to 60 wt % of a bismaleimide resin; 1 to 10 wt % of a liquid rubber resin; and 20% to 50% by weight of filler.
2. The resin composition according to claim 1, characterized in that The bismaleimide resin includes DCPD-BMI, KI-50P, KI-70 or a combination thereof.
3. The resin composition according to claim 1, characterized in that The liquid rubber resin includes LDM-03-07, LDM-02, 1,2-SBS or a combination thereof.
4. The resin composition according to claim 1, characterized in that The invention also includes 0.1 wt % to 3 wt % of a coupling agent and 0.1 wt % to 2 wt % of a catalyst.
5. The resin composition according to claim 4, characterized in that Also included is 10 to 20 wt % of a flame retardant.
6. An electronic component, characterized in that: include: A substrate formed from the resin composition according to any one of claims 1 to 5.
7. The electronic component according to claim 6, characterized in that: The glass transition temperature of the substrate is greater than or equal to 250°C.
8. The electronic component according to claim 6, characterized in that: The substrate has a dielectric loss of less than or equal to 0.002 at a frequency of about 10 GHz.
9. The electronic component according to claim 6, characterized in that: The substrate has a dielectric constant less than or equal to 3.2 at a frequency of about 10 GHz.
10. The electronic component according to claim 6, characterized in that The substrate is a copper foil substrate.